2020
DOI: 10.1002/jor.24927
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal microbiology: The utility of the microbiome in orthopedics

Abstract: The past 15 years have witnessed a renaissance in the study of the microbes that colonize the human body. The vast majority of the human microbiome resides within the gut. Alterations to the gut microbiome have been associated with the pathogenesis and progression of wide‐ranging diseases throughout the body—including atherosclerosis, depression, and obesity. Our understanding of the effects of the gut microbiome on the musculoskeletal system remains in its infancy, but preclinical work has demonstrated an eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Mitigating alterations in the composition of the gut microbiota using prebiotic fiber and exercise have been demonstrated to be protective from OA 2 , 20 , supporting the notion that modification of the gut microbiome could provide an attractive, minimally-invasive therapeutic target for cartilage damage 15 , 21 , 22 . For example, germ free mice demonstrate less bone loss in response to non-invasive load-based injury compared to conventional controls 23 .…”
Section: Discussionmentioning
confidence: 81%
“…Mitigating alterations in the composition of the gut microbiota using prebiotic fiber and exercise have been demonstrated to be protective from OA 2 , 20 , supporting the notion that modification of the gut microbiome could provide an attractive, minimally-invasive therapeutic target for cartilage damage 15 , 21 , 22 . For example, germ free mice demonstrate less bone loss in response to non-invasive load-based injury compared to conventional controls 23 .…”
Section: Discussionmentioning
confidence: 81%
“…With the in-depth study of intestinal flora, some orthopedic researchers have turned their attention to intestinal flora and orthopedic diseases. Many studies have confirmed the close relationship between intestinal flora and musculoskeletal health and diseases, [20][21][22][23] Tousen et al [24] By giving isoflavones and fructooligosaccharides that can change intestinal flora to osteoporotic Wistar rats after ovariectomy, after 90 days of culture, it is found that compared with sham operation group, the total mineral density of femur and metaphysical bones of…”
Section: Introductionmentioning
confidence: 97%
“…With the in-depth study of intestinal flora, some orthopedic researchers have turned their attention to intestinal flora and orthopedic diseases. Many studies have confirmed the close relationship between intestinal flora and musculoskeletal health and diseases, [20–23] Tousen et al [24] By giving isoflavones and fructooligosaccharides that can change intestinal flora to osteoporotic Wistar rats after ovariectomy, after 90 days of culture, it is found that compared with sham operation group, the total mineral density of femur and metaphysical bones of Wistar rats is significantly increased, and the bone strength is also significantly improved, suggesting that there is a close relationship between intestinal flora and osteoporosis. Therefore, this paper expounds the immune mechanism, endocrine mechanism, brain-gut axis mechanism, the effect of metabolites on intestinal flora and the regulatory mechanism of osteoporosis.…”
Section: Introductionmentioning
confidence: 98%
“…Disruptions in the gut microbiota, as may occur through antibiotic therapy, stress, or an unbalanced diet [ 2 ], have been linked with numerous diseases including inflammatory bowel disease [ 3 ], metabolic syndrome [ 4 ], asthma [ 5 ], cardiovascular diseases [ 6 ], and bone-associated pathologies, such as osteoporosis [ 7 , 8 ] and osteoarthritis [ 9 , 10 ]. Conversely, positive interventions, in the form of prebiotics, probiotics, or postbiotics, have proven health benefits to the host if administered in appropriate amounts [ 11 , 12 ]. Many of the beneficial effects of the microbiota are mediated by the postbiotic short-chain fatty acids (SCFAs) acetate, propionate, butyrate, and valerate, which are generated by the gut bacteria upon fermentation of dietary fibers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%